HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU TERHADAP KEMAMPUAN HASIL SERVIS ATAS BOLA VOLI PADA TIM PUTRI SMP NEGERI 4 PEKANBARU - Rina Rina; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: based on observations of the author at the time of carrying out Observations On the country Junior women's team 4 Pekanbaru, a description of the research data is made up of two variables namely variables i.e. non arm and shoulder muscular strength (X) variable and tied to the ability of the results of the service top (Y). Power measurement is performed with the ekspanding dynameter against 8 samples, obtained the best results 35 the worst results, 20, the average (mean) 27,75 (28), Byway of baku (standard deviation) 4.98 (5), based on the frequency distribution table on top of 8 samples, It turns out there are two person sample (25%) have the results strength with 20-23 value with span categories less, then 2 people (25%) samples have the results strength with 24-27 value with span categories less, and 2 samples (25%) have results strength with 28-31 value with span categories are, then 2 people (25%) of the sample had a value of stretch results strength with 32-35 with categories either. Measurement of the results of the tests carried out using the servicing servicing against 8 people sample, obtained the best result of 21, the worst result of 16, the average (mean) 18.5, Byway of baku (standard deviation) 160. This first testing i.e. There is a relationship between muscle strength arm and shoulder with the results service. Based on the analysis done, then gained an average strength of arm and shoulder muscles 27.75 (28) with the raw Byway 4.98 (5). From the description above retrieved analysis correlation between power arm and shoulder muscles results service, where significant extent on rtab (0.05) = 0.707 means rhitung (0.984) < rtab (0.707) then there is a significant relationship.Key Words: Muscle Strength Arm And Shoulders, Servicing Over